Islamic Republic of Afghanistan : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Afghanistan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Islamic Republic of Afghanistan's Request for Disbursement Under the Rapid Credit Facility. The disbursement will help meet the urgent fiscal and balance of payments needs stemming from the coronavirus disease 2019 pandemic, catalyze donor support, and shore up confidence. The pandemic is inflicting heavy damage on Afghanistan's economy, which is expected to contract sharply in 2020, imperiling the livelihood of a significant segment of the population. The authorities are taking emergency measures to contain the pandemic and its immediate social and economic impact. Substantial donor financing is urgently needed to help Afghanistan cover these fiscal and external financing needs which could increase further if the pandemic and its economic impact intensify. Beyond the immediate response, the authorities are committed to safeguarding macroeconomic stability and promoting inclusive growth. The central bank continues to focus on price stability. The IMF stands ready to assist Afghanistan as it battles the pandemic and to support its economic reforms going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet